MARRIAGE COUNSELING (Studi Terhadap Peran Badan Penasihatan, Pembinaan, dan Pelestarian Perkawinan dalam Membentuk Keluarga Samara) - Suparlan, Suparlan (Jurnal Muhakkamah, 2019)
Islam encourages a person, both male and female, to marry if he already has material and mental readiness (psychic). The suggestion is basically as a form of maintaining Islam for human glory. In the sense of the word, marriage - as the initial door to forming a family - is something that has always been a desire for everyone, both men and women. Because, with marriage, men and women can get along nobly in family life as beings who have glory. BP-4 as an official marriage counseling institution in Indonesia on the one hand has an important and large role in forming a sakinah, mawaddah, and rahmah family. But on the other hand, the existence of BP-4 is still not optimal. That is caused by various aspects, both aspects of legal substance, legal structure, and legal culture. Thus, according to the speaker, in the future it may be necessary to have maximum cooperation between BP-4 as a Family Counseling Agency with the Social Service and BKKBN, or other agencies to create a prosperous, prosperous and healthy family. In addition, Non-Government Family Counseling Institutions are needed as BP-4 partners to maximize the duties of BP-4 itself.